Gene Therapy: Encapsulation, Visualization and Expression of Genes with Biomimetically Mineralized Zeolitic Imidazolate Framework‐8 (ZIF‐8) (Small 36/2019). Issue 36 (4th September 2019) - Poddar, Arpita; Conesa, José J.; Liang, Kang; Dhakal, Sudip; Reineck, Philipp; Bryant, Gary; Pereiro, Eva; Ricco, Raffaele; Amenitsch, Heinz; Doonan, Christian; Mulet, Xavier; Doherty, Cara M.; et al.
Abstract : Gene therapy utilizing non‐viral delivery systems still lags behind its viral counterpart despite being the safer method. In article number1902268, Ravi Shukla and co‐workers explore the potential of metal–organic frameworks (MOFs) for gene delivery. The most fundamental aspect of DNA, its ability to translate into proteins, is investigated to determine the suitability of MOFs as delivery agents for gene therapy. The cover illustrates DNA embedded in the meshwork of ZIF‐8. Kate Rowe is acknowledged for framework photograph.